The numerical research of the flow in the inlet of the highhead hydraulic turbine - Rezvaya, Kseniya Sergeevna; Krupa, Evgeniy Sergeevich; Drankovskiy, Viktor Eduardovich; Potetenko, Oleg Vasilyevich; Tynyanova, Irina Ivanovna (НТУ "ХПІ", 2017)
3D-methods for the calculation of flow are used in this work. The solid model of the inlet is created. The mesh of the tetrahedral type is constructed. The boundary conditions for the calculations in the program are given, namely: the rate in inlet of the spiral casing and pressure on an exit. The choice of the turbulence model was based on the tasks that were set earlier. The results of numerical research of three-dimensional flow of a fluid flow in the high-head radial-axial hydraulic turbine are presented. Calculations are conducted for prognostication of descriptions and optimization of form of water passage of hydraulic turbines. The calculation of coefficient of losses of kinetic energy in the elements of inlet of hydraulic turbine is conducted. The total energy losses in the inlet of the water passage using different applied program packages are determined. The comparison of the data, which was obtained by in the calculations and the experimental data, is produced. The distributions of the total pressure and static pressure are presented in this paper. The velocity distribution in the meridional sections is presented. The complex nature of fluid flow is described. The secondary fluid flow in the spiral casing of the hydraulic turbine is confirmed by calculations. This secondary motion in the spiral casing of the hydraulic turbine appears due to the complexity of the fluid flow. Conclusions about the results of the three-dimensional calculations are made. Using special programs in the design of hydraulic turbines can reduce the technological resources and time.

Представлені результати чисельного дослідження тривимірної течії потоку рідини в високонапірній радіально-осьовій гідравлічній турбіні. Визначено втрати повної енергії в підвідних елементах проточної частини за допомогою різних пакетів прикладних програм. Проведено порівняння даних, отриманих при розрахунках та експериментальних стендових даних. Описано складний характер течії потоку рідини. Розрахунковим шляхом підтверджено наявність вторинний рух рідини в спіральній камері гідравлічної турбіни. Порівняно результати, які отримані шляхом розрахунку із застосуванням пакетів програм а також експериментальні данні.
Чисельне дослідження потоку в підводі високонапірної гідротурбіни
Keywords: hydraulic turbine; inlet; k-ε model of turbulence; coefficient of losses; distribution of pressure; distribution of velocity; secondary motion; гідравлічна турбіна; підвідна частина; k-ε модель турбулентності; коефіцієнт втрат; розподіл тиску; розподіл швидкості; вторинний рух